Strategi Integrasi Terminal Pinang Baris dalam Mendukung Sistem Transportasi Publik Berbasis TOD di Medan - Nursahlima, Dwi; Marpaung, Beny OY (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines the operational challenges faced by Pinang Baris Terminal, a Type A terminal in Medan, particularly flooding in the bus parking area and limited parking capacity that hinder transportation efficiency. The research aims to integrate the terminal into a Transit-Oriented Development (TOD) framework to create a sustainable, efficient, and walkable transportation hub. A descriptive qualitative method with a case study approach was applied, using field observations, passenger flow analysis, and infrastructure evaluation as primary data, alongside literature reviews of TOD best practices, transport regulations, and terminal design standards as secondary data. The analysis employs the 3D TOD Model—Density, Diversity, and Design—combined with New Urbanism principles to develop an integrated design concept. The results propose a multi-level, mixed-use terminal design that addresses flooding through elevated structures and improved drainage systems. Parking capacity is enhanced via vertical expansion, while integration with commercial spaces, green open areas, and pedestrian-friendly pathways supports accessibility and urban connectivity. The spatial configuration promotes walkability and encourages public transport use. The findings indicate that TOD integration can improve terminal operational efficiency by up to 40% and generate positive economic spillover effects in the surrounding area. The study recommends phased implementation, prioritizing flood mitigation infrastructure and supportive policies for mixed-use development. Overall, the research contributes a climate-responsive TOD model adaptable to similar urban transportation challenges in Indonesia.